2001
DOI: 10.1103/physreve.63.036305
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude measurements of Faraday waves

Abstract: A light reflection technique is used to measure quantitatively the surface elevation of Faraday waves. The performed measurements cover a wide parameter range of driving frequencies and sample viscosities. In the capillary wave regime the bifurcation diagrams exhibit a frequency independent scaling proportional to the wavelength. We also provide numerical simulations of the full Navier-Stokes equations, which are in quantitative agreement up to supercritical drive amplitudes of ε ≃ 20%. The validity of an exis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
(60 reference statements)
2
18
0
Order By: Relevance
“…(iv) We have only taken a few from the many experimental points by Wernet et al (2001), namely those points in which the wavelength of the excited waves was small Edwards (1994) are unpublished and are taken from Kumar & Tuckerman (1994), Kumar (1996) and Cerda & Tirapegui (1998). compared with the container depth.…”
Section: Highly Viscous Limitmentioning
confidence: 99%
“…(iv) We have only taken a few from the many experimental points by Wernet et al (2001), namely those points in which the wavelength of the excited waves was small Edwards (1994) are unpublished and are taken from Kumar & Tuckerman (1994), Kumar (1996) and Cerda & Tirapegui (1998). compared with the container depth.…”
Section: Highly Viscous Limitmentioning
confidence: 99%
“…Until about a decade ago, the Faraday instability had been intensively studied in Newtonian fluids [4][5][6]8,9]. Only recently have vertically vibrated complex fluids been the subject of experimental [10][11][12][13][14] and theoretical research [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, if the fluid is too viscous one cannot observe the anomalous mode. Since it has been showed that for viscous fluids the instability pattern is independent on the shape of the container (Edwards and Fauve, 1993;Wernet et al, 2001), one can think that if the fluid is too viscous, the dissipation damps the resonance. By taking into account the experimental observations presented above, we can support our conjecture by considering the cell as a two-dimensional system and by decomposing the wavenumber of the excited mode, , in two components, a longitudinal one, kx l=nπ with n=0,1,2,3,… and a transverse one, ky d=qπ, by taking q=2.…”
Section: Discussionmentioning
confidence: 99%
“…When the acceleration exceeds a threshold value, surface waves appear oscillating at half the forcing frequency and with a critical wave number k. In the recent years, this system has been widely studied, both experimentally and theoretically, since it is a paradigm experiment for the investigation of pattern formation (Kumar and Tuckerman, 1994;Edwards and Fauve, 1993;Wernet et al, 2001), spatio-temporal phenomena (Epstein and Fineberg, 2004) and localized oscillations (Arbell and Fineberg, 2000).…”
Section: Introductionmentioning
confidence: 99%